Introduction to Dossier. Class Configurations, Work, and Capital Interests in Latin America - Marega, Magali; Vogelmann, Verónica; Vitali, Sofía (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2019)
Introduction to Dossier "Class Configurations, Work, and Capital Interests in Latin America".